Peningkatan Atensi pada Anak ADHD dengan Teknik Self Instruction - Prabawat, Fransisca Anindya Mariesta; Ditasari, Niken Nurmei (Philanthropy: Journal of Psychology, 2018)
The aim of this study is to analyze the impact of self instruction method on attention improvement. Hypothesis of this study is self instruction method can increase attention of ADHD children.the subjects in this study are children which have been diagnosed with ADHD withage of 12 years old. Three behavior are observed, they are keep attention to the teacher, follow the teacher expression, and do the task until done according to teacher asking without leaving the chair. ABA design was used as study s design. Statistical analysis in the study was done using t-test method. Based on statistical result it was found that to t0 (5,143) >ttab(2, 145) which can be concluded that treatment with self instruction method was significantly increase the attention of ADHD children.